A maternal screen for genes regulating Drosophila oocyte polarity uncovers new steps in meiotic progression. - Barbosa, V.; Kimm, N.; Lehmann, R. (Genetics, 2007)
Meiotic checkpoints monitor chromosome status to ensure correct homologous recombination, genomic integrity, and chromosome segregation. In Drosophila, the persistent presence of double-strand DNA breaks (DSB) activates the ATR/Mei-41 checkpoint, delays progression through meiosis, and causes defects in DNA condensation of the oocyte nucleus, the karyosome. Checkpoint activation has also been linked to decreased levels of the TGFalpha-like molecule Gurken, which controls normal eggshell patterning. We used this easy-to-score eggshell phenotype in a germ-line mosaic screen in Drosophila to identify new genes affecting meiotic progression, DNA condensation, and Gurken signaling. One hundred eighteen new ventralizing mutants on the second chromosome fell into 17 complementation groups. Here we describe the analysis of 8 complementation groups, including Kinesin heavy chain, the SR protein kinase cuaba, the cohesin-related gene dPds5/cohiba, and the Tudor-domain gene montecristo. Our findings challenge the hypothesis that checkpoint activation upon persistent DSBs is exclusively mediated by ATR/Mei-41 kinase and instead reveal a more complex network of interactions that link DSB formation, checkpoint activation, meiotic delay, DNA condensation, and Gurken protein synthesis.